Preparation of oxygen-enriched hierarchically porous carbon by KMnO4 one-pot oxidation and activation: Mechanism and capacitive energy storage. (20th January 2019) - Qiu, Daping; Guo, Nannan; Gao, Ang; Zheng, Lun; Xu, Weijia; Li, Min; Wang, Feng; Yang, Ru
Abstract: Oxygen-enriched hierarchical porous carbon (OHPC) is synthesized via an environmentally friendly, facile and cost-effective one-pot pyrolysis of KMnO4 @cork composites. The evolution path of KMnO4 and its activation mechanism at various stages have been preliminarily understood based on the analysis of XRD data of samples with different synthetic conditions. Benefiting from the synchronous oxidation modification and activation of KMnO4, the as-synthesized OHPC demonstrated a high oxygen content and hierarchical porous structure. The electrochemical measurements revealed that the OHPC electrode in a 6 M KOH three-electrode system exhibited a high specific capacitance of 290 F g −1 at 0.2 A g −1, and retained 210 F g −1 even at 70 A g −1, with a high capacitance retention of 72.4%. The excellent electrochemical performance can be ascribed to the special hierarchical porous structure and abundant content of oxygen (16.8 at%). Further feasibility characterization confirmed that the constructed OHPC-based symmetric supercapacitors demonstrated a high specific capacitance of 242 F g −1 and excellent durability after 10000 cycles (95.2% capacitance retention) in an alkaline 6 M KOH electrolyte, and displayed a high energy density of 14.7 Wh kg −1 in neutral 1 M Na2 SO4 . This study opens up an environmentally friendly, facile and cost-effective route for the synthesis of biomass derived carbons for advanced energy storage. Graphical abstract: